(untitled) (GnosisWisdom, 2022)
The socioeconomic analysis in maize (Zea mays) agroforestry systems was evaluated in the Populated Center of Santa María (Daniel Hernández, Tayacaja), therefore the main objective of this study was to evaluate the socioeconomic analysis in maize (Zea mays) agroforestry systems.) interrelated with the social, economic and environmental factors of the maize growers in the Santa Maria Populated Center, in the district of Daniel Hernández Tayacaja-Huancavelica, Peru. The total content of corn crops in agroforestry systems was interrelated with the social, economic and environmental factors of the plots and families that cultivate it. The research was carried out using Likert-type questionnaires surveying 25 farmers; farmers from the social approach, show positive attitudes of satisfaction in the application of the SAF of corn crops, motivation for agriculture (52%), working with the family (12%) and in the economic approach they reflect dedicating themselves to the SAF of corn crops (40%). Corn producers do not receive any benefit for environmental services, managing their corn plots, they only obtain seeds.